EDUKASI DIGITAL MARKETING MENUJU UMKM KREATIF DI DESA TAMAN KECAMATAN GRUJUGAN - Aji Ahmad Amrozi; Agus Afandi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
The role of Usaha Mikro, Kecil, dan Menengah (UMKM) in national economic growth and job creation is crucial, especially in areas with limited access to information technology. In Desa Taman, Kecamatan Grujugan, significant challenges exist in the adoption of digital technology by UMKM operators, leading to limitations in product marketing and business management. Observations by the Kuliah Kerja Nyata (KKN) Persemakmuran Eks. IAIN Sunan Ampel identified two primary issues: a low level of understanding of UMKM concepts and regulations according to Law No. 20 of 2008, and educational limitations that affect managerial skills and the adoption of digital technology. To address these issues, a digital marketing socialization activity was conducted to enhance UMKM owners' knowledge about digital-based marketing. The methods employed included presenting material on digital marketing, covering definitions, objectives, and benefits, as well as a question-and-answer session to assess participants' understanding